Update on heat detection aids - Stevenson, Jeffrey S.; Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
Poor heat detection is a major cause of reproductive failure in most dairy herds. About one-half of the heat periods are undetected, resulting in prolonged calving intervals. In many cases, the problem is serious enough that some producers have compromised their breeding goals by utilizing natural mating exclusively or maintaining clean-up bulls. The result of these compromises means loss in genetic superiority of future replacement heifers and the potential for serious injury or death of farm help or family.
Keywords: Dairy; Heat detection; Estrus